The initiation and development of combustion under cold idling conditions using a glow plug in diesel engines - Li, Qile; Shayler, Paul J.; McGhee, Michael James; La Rocca, Antonino (SAGE, 2016)
Factors determining the success or failure of combustion initiation using a glow plug have been investigated through experimental work on a single cylinder, common rail diesel engine with a geometric compression ratio of 15.5, and a quiescent combustion bomb with optical access. A glow plug was required to avoid engine misfires when bulk gas temperature at the start of injection was less than 413 C. The distance between the glow plug and the spray edge, the glow plug temperature, and the bulk gas temperature were important factors in meeting two requirements for successful ignition: a minimum local temperature of 413 C and a minimum air/fuel vapour equivalence ratio of 0.15–0.35.